Doing foster family with young refugees: Negotiations of belonging and being at home. (26th May 2021) - Mörgen, Rebecca; Rieker, Peter
Abstract: Unaccompanied minor refugees are regularly placed with foster families, and this residential context is sometimes assessed as especially appropriate to the needs of these young persons. The transition into a foster family is often accompanied by various changes as well as questions concerning feelings of belonging. These questions are the focus of this study, which considers the perspectives of young refugees and their foster parents. The analysis shows that 'belonging' and 'being at home' are thought of as dimensions of 'doing family' that change situationally and are negotiated with others.